(untitled) (Research, Society and Development, 2022)
The objective of this work was to evaluate the influence of the patients’ diet on the strength degradation of Nickel-titanium closed springs. Forty 9mm nickel titanium springs from the Morelli brand were used, divided into 2 groups of 20 according to the immersed solution. These springs were stretched to 100% of their original length and kept in devices immersed in recipients with the evaluated solutions (artificial saliva and distilled water with coke). The resulting forces were measured with a precision orthodontic dynamometer (grams) performed shortly after initial distension (T0) and after 28 days of distension (T1), then at the end of 20 and 30 months, T2 and T3 respectively. To compare times and groups, analysis of variance for repeated measures and Tukey’s test were used. A significance value of 5% was adopted for the analyses. In the intragroup results, the springs showed a significant decrease in force between the evaluated periods. When comparing the values ​​of forces between the groups (artificial saliva vs coke) in each period, it was observed that there was no significant difference, indicating that the type of solution did not influence the degradation of the forces of the springs. It was concluded that, regardless of the ingestion of liquids such as coke, NITI springs show significant strength degradation during the first 3 months. It is necessary to measure the forces of the springs during orthodontic treatment, aiming to establish an adequate force for movement and optimization of treatment time.